2015
DOI: 10.5929/2015.5.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Twitter in the Creation of Educational Professional Learning Opportunities

Abstract: This study sought to examine how educators are using Twitter to increase their professional learning opportunities beyond the boundaries of traditional professional development offers, and whether educators feel a greater sense of fulfillment receiving professional development through networking and community learning than they do through traditional means of learning. A population of 160 educators-105 females and 55 males between the ages of 22 and 65-were surveyed using education related hashtags on Twitter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 6 publications
3
20
0
3
Order By: Relevance
“…In comparison, school MSs have received sparse interest (Stemler, Bebell & Sonnabend, 2011;Ayers, 2015), while failing to provide an in-depth qualitative analysis of how MSs manifest in daily practice. In contrast to MSs, the topic of CPDL is associated with a large and growing body of literature, gaining further momentum via popular informal platforms of professional development such as social media (Sie et al, 2013;Ross, Maninger, LaPrairie & Sullivan, 2015;Stevenson, Hedberg, O'Sullivan & Howe, 2016;Vlachopoulos & Makri, 2019), and calls to increase research-based practice in schools (Cordingley, 2015). Only two studies to date link faculty development to school vision (Legorreta, Kelley & Sablynski, 2006).…”
Section: Introduction and Rationalementioning
confidence: 99%
“…In comparison, school MSs have received sparse interest (Stemler, Bebell & Sonnabend, 2011;Ayers, 2015), while failing to provide an in-depth qualitative analysis of how MSs manifest in daily practice. In contrast to MSs, the topic of CPDL is associated with a large and growing body of literature, gaining further momentum via popular informal platforms of professional development such as social media (Sie et al, 2013;Ross, Maninger, LaPrairie & Sullivan, 2015;Stevenson, Hedberg, O'Sullivan & Howe, 2016;Vlachopoulos & Makri, 2019), and calls to increase research-based practice in schools (Cordingley, 2015). Only two studies to date link faculty development to school vision (Legorreta, Kelley & Sablynski, 2006).…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Although the use of social media expands educator education beyond "one-size-fits-all, sitand-get professional development" (Ross, Maninger, LaPrairie, & Sullivan, 2015), studies have shown that educators' participation in such communities is largely uneven. For example, a 2017 study by one of the authors (withhold for review) found that the online synchronous chat that occurred among the members of a Twitter community for educators was dominated by a group of active members.…”
Section: Introductionmentioning
confidence: 99%
“…This is because it is easy and free to use and can extend the reach of a traditional workshop (Ross, Maninger, LaPrairie, & Sullivan, 2015). Regarding isolated international schools who need various means to provide professional development other than sending teachers to workshops or bringing in specialists, social media tools could provide a route that is free and easy to use.…”
Section: Personal Learning Environments As a Solution To The Problemmentioning
confidence: 99%
“…This was one way that shows a teacher will use a tool that they find most useful. Ross, Maninger, LaPrairie, & Sullivan, (2015) found the use of social media tools such as Twitter might elevate the chance of successful implementation of a PLN because it is easy and free to use. For P4, Facebook was her easier to use platform that was helping her successfully implement her PLN.…”
Section: International School Teacher Plns Model Online Communities Omentioning
confidence: 99%
See 1 more Smart Citation